Molecular cloning and sequence of the pres domain of human hepatitis b surface antigen - Quyen, Dong Van; Khang, Dinh Duy; Gyu, Yu Gyun (Academia Journal of Biology, 2015)
By using nested PCR with specific primers, we have amplified and cloned the preS domain, including 170 nucleotides of the S domain of the hepatitis B virus surface antigen (HBsAg) from human liver tumor biopsies. The sequence of this isolated preS domain was compared with other preS domains from the International Gene Bank Database. The identity ranges from 90 to 97%. These results suggested that the HBV strain isolated from Vietnamese patient was an adr subtype.